Women living in the region under an emergency command post are experiencing delays in reaching health facilities: a multi-center cross-sectional study - Besfat Berihun Erega; Abebaye Adigo Zeru; Begizew Yimenu Mekuriaw; Rahel Birhanu Arage; Yitayal Ayalew Goshu; Wassie Yazie Ferede; Mulat Ayele; Gizachew Yilak; Befkad Derese Tilahun; Habtam Desse Alemayehu; Eyob Shitie Lake (BMC, 2024)
Abstract Introduction The time between seeking emergency care and receiving the first healthcare service is referred to as delays in reaching health facilities. Delay in reaching health facilities had three main sub-themes in different studies. These include (i). Availability of transportation and infrastructure, (ii). Distance from health facilities and (iii). Lack of finance for transportation. Although there are plenty of findings about maternal delays in reaching health facilities, studies do not address the delay situation of women in conflict zones all over the world. In Ethiopia, specifically, we saw women delayed in healthcare service due to restricted movement and closure of roads, even for ambulances, at night time. Methods A multi-center cross-sectional study was conducted among mothers attending public health facilities in the south Gondar zone, Ethiopia from September 01/2023 to April 30/2024. The data was collected by four BSc degree-holder midwives, using structured questionnaires after training was given for a day in each hospital. A pretest using 5% of the sample size was conducted. Descriptive statistics, and multivariable logistic regression analyses were used to identify factors associated with delays in reaching health facilities. Variables having p-value ≤ 0.2 in the bi-variable analysis were fitted into multiple logistic regression models. Result The prevalence of delay in reaching health facilities among women who are living in the region of emergency command post was 54.9% CI (42.04-59.87%). Living in rural areas, non-availability of public transport during the armed conflict, labor onset at nighttime, road closures by the armed forces, and non-availability of ambulances were the factors that contributed to the delay during the emergency command post. Conclusion The magnitude of delay in reaching health facilities among women who are living in the region of emergency command post was high.